IMPLEMENTASI PROSES MANAGEMEN PENJUALAN PADA UKM - Arifin Djakasaputra; Nadira Aulia Putri; Yunia Arinda Jayanti (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
Sales is one of the important components in the marketing system that plays a role in generating revenue. This activity aims to provide business owners with knowledge about the sales process to increase sales of their products. The partners involved in this activity are culinary businesses in Jambi. The method used was training and socialization, which included an introduction to the sales process, starting from finding potential buyers, identifying prospects, qualifying prospects, to making sales. Evaluation of the activity showed that the training went smoothly and succeeded in improving partners' understanding of the sales process, so that they can make improvements in maintaining sales continuity in the future.